2017
DOI: 10.1016/j.lungcan.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab-induced interstitial lung disease analysis of two phase II studies patients with recurrent or advanced non-small-cell lung cancer

Abstract: Although the risk factors for nivolumab-induced ILD were not identified, careful monitoring including imaging examinations is important in preventing the worsening of ILD in patients receiving nivolumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
116
3
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(127 citation statements)
references
References 9 publications
7
116
3
1
Order By: Relevance
“…The synergistic effect of osimertinib and nivolumab may contribute to the high incidence of ILD. Recently, Kato et al reported that nivolumab‐induced ILD was observed in 7.2% of patients, with radiological imaging showing a pattern of organized pneumonia or nonspecific interstitial pneumonia without traction bronchiectasis . The radiological findings of ILD in our study also revealed a pattern of organized pneumonia.…”
Section: Discussionsupporting
confidence: 76%
“…The synergistic effect of osimertinib and nivolumab may contribute to the high incidence of ILD. Recently, Kato et al reported that nivolumab‐induced ILD was observed in 7.2% of patients, with radiological imaging showing a pattern of organized pneumonia or nonspecific interstitial pneumonia without traction bronchiectasis . The radiological findings of ILD in our study also revealed a pattern of organized pneumonia.…”
Section: Discussionsupporting
confidence: 76%
“…Kato et al . reported seven of eight patients had a pattern of OP or nonspecific interstitial pneumonia . Naidoo et al .…”
Section: Discussionmentioning
confidence: 93%
“…First, the majority of patients in the ILD group had a low preexisting ILD extent score; therefore more than two‐thirds of the patients in the ILD group could be treated with nivolumab as second‐line chemotherapy. Second, nivolumab‐related pneumonitis resulted in low mortality and was more responsive to immunosuppressive agents than the pneumonitis induced by cytotoxic chemotherapies or molecular‐targeted agents . Finally, frequent chest radiographic examination of preexisting ILD might have led to the early detection of nivolumab‐related ILD, but may also have partially contributed to the higher incidence of nivolumab‐related pneumonitis in the ILD group.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, immune checkpoint inhibitors (ICIs) have been used for the treatment of non‐small cell lung cancer (NSCLC) in clinical practice . The incidence of ICI‐related pneumonitis, including some fatal cases, is reported as 1–12% . In contrast to cytotoxic chemotherapy or molecular‐targeted agent‐related pneumonitis, most ICI‐related pneumonitis patients appear to be sensitive to treatment with corticosteroids; however, the risk of ICI‐related pneumonitis in patients with preexisting ILD is unknown …”
Section: Introductionmentioning
confidence: 99%